Produtividade, composição bromatológica e dinâmica do perfilhamento da brachiaria híbrida convert HD364 sob alturas de corte - Alves, Emanuel Stival Godoy (2016)
This study aimed to verify if different height management influence in productive characteristics, bromatological and tillering dynamics of Brachiria Hibrid Convert HD 364. The treatments were four cut heights: 25, 30, 35 and 40 cm with 15 cm residue and three repetitions of each treatment. The distribution in the experimental filed was completed randomized in 12 parcels. Were evaluated production of total dry matter, leafs and culm. Bromatological composition was evaluated in leafs, culms and whole plant. From tillering dynamics were evaluated appearance rate (TAP), surveillance (TSOB), mortality (TMOR), proportion among appearance rate and mortality and tiller stability index (IEST). Dry matter production of whole plant and leafs of Brachiária hybrid Convert HD364 was influenced by cut height with higher production obtained in 40 cm. No differences among whole plant, leafs and cull, were found managing heights varying between 25 and 40 cm in evaluated dry matter content, mineral matter, neutral detergent fiber and acid detergent fiber. Height cut influenced in crude protein content only at 35 cm. Fractions of B. Convert HD364 cull and whole plant presented differences in bromatological composition being observed higher crude protein and mineral matter in leafs and higher neutral detergent fiber and acid detergent fiber in culls. Pastures of B. Convert HD364 managed with varying height of 25 to 40 cm, showed no differences in tillering dynamics, surveillance and stability index. Furthermore, bromatological composition was no compromised by cut heights, being this cultivar suitable to be used in ruminant alimentation.